Analisis Tingkat Kepuasan Konsumen Berdasarkan Kualitas Pelayanan pada Pengunjung Objek Wisata Pantai Pulau Merah Kabupaten Banyuwangi - Mohamad Jajang I; Diah Yulisetiarini; Hadi P (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This article aim to anayze the level of satisfaction of customer on the quality of services that includes physical evidence, dependability, responsiveness, assurance, and empathy on subjects tourist Red Island Beach. The population in this research was visitors of The Red Island Beach. Sampling method used was non-probability sampling namely purposive sampling with the number of respondents as much as 108 people. Variables used the quality of services. The analysis methode uses Service Quality (SERVQUAL).The results demonstrates that 1) physical evidence has eight indicator which all indicators showed satisfaction visitors of Red Island Beach.2) dependability indicator having two roomates they showed satisfaction visitors of Red Island Beach. 3) responsiveness indicator having two roomates they showed satisfaction visitors of Red Island Beach. 4) assurance indicator having two roomates they showed satisfaction visitors of Red Island Beach .5) empathy have five indicator roomates showed satisfaction reviews those five visitors of coastal islands red. Keyword: Consumer Satisfaction, Quality of Service, Servqual, Wilcoxon Signed Rank Test.